Review the Concept of Al-‘Adah Al-Muhakkamah on Tradition “Batal Wudhu” the Traditional Wedding of Ternate People in Ternate - Nur Azizah Rahman; Marwa Anjamila Tarima; Harun Ginoni; Muhrim Djakat (Jurnal Ilmiah Al-Syir'ah, 2022)
The procession of “cancel ablution” at the traditional wedding of the people of Ternate became one of the traditions that must be done. This procession is understood by society as a change of status between men and women into husband and wife. This procession raises the understanding that the husband and wife do not have a prohibition on touching hands during prayer because there is already a “cancellation of ablution” when married. Suppose you look at the rules of the prohibition of contact that is not a mahram as a condition for the validity of prayer. In that case, you have different opinions, and the law of the prohibition of contact for non-mahrams does not fall just because there has been a change in marital status. Starting from this understanding attracted researchers to study how the implementation of “cancel ablution” in traditional marriages of the people of Ternate City and how al-‘adah al-muhakkamah studied this procession. This study uses the qualitative descriptive verification method by describing the pattern of tradition in the community of Ternate city and then verifying correctly or distorting this procession to be applied by the community using the concept of Al-‘adah al-muhakkamah. This study found that the community procession ‘cancel ablution’ is a hereditary tradition and has developed since the first. The procession of” cancel ablution,” which is understood by the public, is of two forms: first, some understand this procession as a form of legalization and changes in mahram relations between men and women. Second, as a gift of prayer to the wife named ‘Paha ngoma-ngoma’ by placing her hands on the wife’s crown while praying. Analysis using Al’adah Al-muhakkamah makes the first form to be distorted. It enters the category of’adah fasid or ‘urf fasid while ‘Paha ngoma-ngoma’ can be ‘adah Shahih or ‘urf Shahih is justified, then the procession of “paha ngongoma” is applied, not “ablution void.”